Hubungan kadar kolesterol total dengan kejadian peripheral artery disease pada penderita diabetes melitus - Novita Sabila; Okti Sri Purwanti (Holistik Jurnal Kesehatan, 2024)
Background: One of the countries facing the problem of non-communicable diseases (NCDs) is Indonesia and they are the cause of 63% of deaths, one of which is diabetes mellitus (DM). Every year, the incidence of DM continues to increase, which can cause chronic complications, peripheral artery disease (PAD). PAD is caused by atherosclerosis in the walls of the leg arteries which can be triggered by the presence of excess cholesterol in the body. Purpose: To analyze the relationship between total cholesterol levels and the incidence of PAD in DM sufferers. Method: The research design used a correlational descriptive design with a cross sectional approach to analyze the relationship between total cholesterol levels and the incidence of peripheral artery disease (PAD) in DM sufferers. The population in this study was 106 DM patients who were hospitalized at UNS Hospital in the period January-August 2023. The sampling technique used purposive sampling, so the total sample was 52 patients without diabetic foot ulcers. Results: The relationship between total cholesterol levels and the incidence of PAD in DM sufferers was tested using the Spearman Rank correlation test which showed a strong correlation (r=0.614) and a significant value (p-value) of 0.001. The test decision is that H0 is rejected and Ha is accepted because the p-value is smaller than 0.05 (0.001<0.05). Conclusion: There is a strong relationship between total cholesterol levels and the incidence of PAD in DM sufferers. Suggestion: DM sufferers can control total cholesterol levels within normal limits by avoiding trigger factors such as cigarette smoke, alcohol consumption and foods high in saturated fat. Sufferers are expected to consume foods high in fiber, such as fruit and vegetables and carry out regular physical activity.   Keywords: Diabetes Mellitus; Peripheral Artery Disease (PAD); Total Cholesterol.   Pendahuluan: Salah satu negara yang menghadapi masalah penyakit tidak menular (PTM) adalah Indonesia dan menjadi penyebab kematian 63%, salah satunya adalah diabetes melitus (DM). Setiap tahun, insiden DM terus meningkat, sehingga dapat menyebabkan komplikasi kronis, peripheral artery disease (PAD). PAD disebabkan adanya aterosklerosis pada dinding arteri kaki yang dapat dipicu oleh keberadaan kolesterol berlebih dalam tubuh. Tujuan: Untuk menganalisis hubungan kadar kolesterol total dengan kejadian PAD pada penderita DM. Metode: Rancangan penelitian menggunakan desain deskriptif korelasional dengan pendekatan cross sectional untuk menganalisis hubungan kadar kolesterol total dengan kejadian peripheral artery disease (PAD) pada penderita DM. Populasi pada penelitian ini adalah pasien DM yang dirawat inap di Rumah Sakit UNS pada periode Januari-Agustus 2023 berjumlah 106 pasien. Teknik pengambilan sampel menggunakan purposive sampling, sehingga sampel total berjumlah 52 pasien tanpa ulkus kaki diabetic. Hasil: Hubungan antara kadar kolesterol total dan kejadian PAD pada penderita DM diuji dengan menggunakan uji korelasi Spearman Rank yang menunjukkan korelasi yang kuat (r=0.614) dan nilai signifikan (p-value) sebesar 0.001. Keputusan uji adalah H0 ditolak dan Ha diterima karena nilai p-value lebih kecil dari 0.05 (0.001<0.05). Simpulan: Terdapat hubungan yang kuat antara kadar kolesterol total dengan kejadian PAD pada penderita DM. Saran: Bagi penderita DM dapat mengontrol kadar kolesterol total dalam batas normal dengan cara menghindari faktor pemicu seperti, asap rokok, konsumsi alkohol, dan makanan dengan lemak jenuh tinggi. Penderita diharapkan dapat mengonsumsi makanan tinggi serat, seperti buah dan sayur serta melakukan aktivitas fisik secara teratur.   Kata Kunci: Diabetes Melitus; Kolesterol Total; Peripheral Artery Disease (PAD).